Orang tua dalam Pembentukan Karakter Kristiani Anak Generasi Alfa - Monica Santosa (Sekolah Tinggi Teologi Torsina Surakarta, 2022)
Generation Alpha is a generation that is very dependent on digital devices. The formation of Christian characters for the Alpha generation is not easy when compared to the formation of Christian characters for previous generations. Based on this, the role of parents in the formation of the Christian character of Alpha generation children is very important. The purpose of this research is to increase the role of parents in forming the Christian character of Alpha generation children, namely as educators, mentors, encouragement, supervisors, and friends so that parents of this generation can play an active role in the formation of their Christian character. Parents can pay more attention to their children's growth and development, especially in forming Christian characters based on the word of God. The method used in this study is a descriptive qualitative approach with a literature review. The results of this study by observing and interviewing parents who have children born in 2010 to date show that most parents are not aware of their role as educators, mentors, encouragers, supervisors, and friends, so parents are confused about carrying out their roles towards the formation of a child's Christian character.AbstrakGenerasi Alpha adalah generasi yang sangat bergantung terhadap perangkat digital. Pembentukan karakter Kristen bagi generasi Alpha tidaklah mudah jika dibandingkan dengan pembentukan karakter Kristen generasi sebelumnya. Berdasarkan hal tersebut, peran orang tua dalam pembentukan karakter Kristen anak generasi Alpha sangatlah penting. Tujuan penelitian ini adalah supaya peran orang tua ditingkatkan dalam pembentukkan karakter Kristen anak generasi Alpha, yaitu sebagai pendidik, peembimbing, penyemangat, pengawas, dan sahabat sehingga orangtua dari generasi tersebut bisa berperan aktif dalam pembentukan karakter Kristen mereka. Orang tua dapat lebih memperhatikan mengenai tumbuh kembang anak terutama dalam hal pembentukan karakter kristen yang berdasar pada firman Tuhan. Metode yang digunakan dalam penelitian ini adalah pendekatan kualitatif deskriptif dengan kajian literatur. Hasil dari penelitian ini dengan melakukan observasi dan wawancara kepada orangtua yang memiliki anak yang lahir pada tahun 2010 hingga saat ini adalah sebagian besar orang tua belum menyadari perannya sebagai pendidik, pembimbing, penyemangat, pengawas, dan sahabat, sehingga orang tua kebingungan dalam melakukan perannya terhadap pembentukan karakter kristen anak.